Problem based learning: arduous yet effective method of teaching law - Mohamad, Nor Asiah (2006)
Problem Based Learning (PBL) has been adopted as an assisted learning approach in the International Islamic University especially for Ahmad Ibrahim Kulliyyah of Laws. The one particular subject which has used PBL as one of the methods of teaching law is Equity and Trust 1 and II. This involves the whole batch of the Year 3, Law students. Though, apparently, law deals with problems and cases thus PBL is certainly the best complementary approach for teaching, the practice seems more cumbersome and not favourable by both, lecturers and students. Nevertheless, the mixed response from both quarters should not hinder the implementation of PBL as an assisted teaching methodology for many reasons. Policy wise, the Ministry of Education and Ministry of Higher Learning has in many occasions emphasized about the needs to inculcate the spirit of team working, imparting soft skills and managerial skill into the students. The alumni survey also proved that employers are more concern with students’ ability to communicate, present ideas, team working and socialize rather than simply judging the students performance based on a piece of paper called result transcript. Thus, PBL though reluctantly accepted by the students, nonetheless, it has to a certain extent, contributed towards producing a wholesome graduate. Therefore, it is sometimes inappropriate or too early to let the students to assess the effectiveness of the methods until them being assessed by their colleagues and superiors in the work field.